PENERAPAN NILAI-NILAI ETIKA DALAM PENGOBATAN HUSADA BALI DI BANDAR LAMPUNG - Dr. Wayan Sukarlinawati, S.P., M.Si. (Veda Jyotih: Jurnal Agama dan Sains, 2023)
Today’s technology, Balinese people still have a cultural heritage with a variety of contents in the form of lontar texts. The two medical systems that are developing in the current millennial era are the Bio-Medical system of medicine and the Bio-Cultural system or traditional medicine. One of these lontar texts is the Usada lontar script which contains traditional Balinese medicinal knowledge. The formulation of the problem in this study is How is the application of ethical values in the treatment of Usada Bali in Bandar Lampung? How was the implementation of the Usada Bali treatment carried out in Bandar Lampung? And what are the implications for oneself, society and government? This study uses qualitative methods, with observation, interviews, documentation and literature. The conclusion in this study is that, the application of ethical values in the treatment of usada Bali in Bandar Lampung uses standard service procedures that are applied to usada Bali treatment in Bandar Lampung through several ethical rules for arriving and returning patients during treatment, including: Ethics for washing hand when coming to visit, greet when new patients arrive and are going home and keep their distance and wait according to the arrival number when patients are going for treatment. The implication is that usada Balinese medicine uses supernatural powers (magico-religious) in the usada Balinese system of medicine, which is a potential advantage for Balians that doctors don’t have. The implication of usada Bali treatment for the government. Usada Bali as a system of Balinese local knowledge and wisdom has a strong enough basic capital to develop.